Design of a portable system for continuous recording of arterial parameters during 24h - Bortolin, Lucas (2013)
The simultaneous measurement of pressure and diameter in a central artery during 24 hours could bring new information about the variability of the arterial mechanical properties. In order to perform these measurements in an animal, it is essential to count with a device that could acquire the signals from the sensors with a proper preconditioning circuit and then transfer them wirelessly to be stored and processed remotely. In this paper we present the prototype of a new portable and autonomous device, capable of being hosted on the animal's back. Preliminary results obtained from a pilot experience in a sheep using the prototype are detailed and limitations are discussed.